2017
DOI: 10.1002/jcb.25667
|View full text |Cite
|
Sign up to set email alerts
|

Diphenyl Diselenide Reduces Oxidative Stress and Toxicity Caused by HSV‐2 Infection in Mice

Abstract: Herpes simplex viruses can cause uncommon systemic complications as acute liver failure (ALT) or urinary tract dysfunctions. Diphenyl diselenide, (PhSe) , a classical studied organic selenium compound, has a novel antiviral action against HSV-2 infection and well-known antioxidant and anti-inflammatory properties. This study aimed to investigate if (PhSe) reduces oxidative stress and systemic toxicity caused by HSV-2 infection in mice. Adult BALB/c mice were pre-treated with (PhSe) (5 mg kg /day, intragastric,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…In fact, over-expression and/or overactivation of SOD-3 are required for the induction of pro-longevity response after mild oxidative injury (Salgueiro et al 2017). In agreement with our results, it has been demonstrated that the treatment with organochalcogen compounds present an antioxidant action in the liver of rats by increasing the activity of SOD-3 and decreasing the generation of reactive species in different disease models (Quines et al 2017, Sartori et al 2017.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, over-expression and/or overactivation of SOD-3 are required for the induction of pro-longevity response after mild oxidative injury (Salgueiro et al 2017). In agreement with our results, it has been demonstrated that the treatment with organochalcogen compounds present an antioxidant action in the liver of rats by increasing the activity of SOD-3 and decreasing the generation of reactive species in different disease models (Quines et al 2017, Sartori et al 2017.…”
Section: Discussionsupporting
confidence: 92%
“…Among the chemical entities containing selenium that have been identified, the chemical form of diselenide stands out as an appealing skeleton for development of new anticancer agents . In particular, diphenyl diselenide (PhSe) 2 has been widely studied and has proven activity as oxidative stress protector, , presenting also cytotoxic activity . In this line of investigation, our research group has explored this chemical entity and the most potent antitumoral structures synthesized in our group containing the diphenyldiselenide moiety corresponds to bis­(4-aminophenyl)­diselenide structure .…”
mentioning
confidence: 99%
“…The GPX and SOD plasma levels increased significantly in Se-supplemented-diet to diabetic rats for one month (Ghaffari et al, 2011). Another study demonstrates that diphenyl diselenide (PhSe) active in contradiction of increased oxidative stress in kidney and liver (Sartori et al, 2017). Pre-treatment with diphenylmethyl selenocyanate found to be the most powerful SOD and CAT inducer (Jayanta Kumar Dasa et al, 2013).…”
Section: Superoxide Dismutasementioning
confidence: 99%